Evaluación del ruido y su relación con la hipoacusia laboral en el área de producción de la empresa Parmalat del ecuador s. A de la provincia de Cotopaxi. Diseño de un sistema de intervención. - Pacheco Jiménez, Wilson Arturo (2017)
Parmalat del Ecuador SA is located in the province of Cotopaxi, Latacunga Cato in the area of Lasso center, which is dedicated to the production and distribution of dairy products, by the very fact of being a manufacturing company processes and positions work involving all kinds of risks, especially in the production area the risk of noise, to take appropriate corrective action is based on an identification and then measure and be able to assess the level of existing noise dose in each work area production and those which can produce as much noise exposure occupational disease and Labor Hearing loss, which is produced by the noise remains in our country and other countries one of the leading causes of occupational diseases shown by the physical factor Noise risk, since there is not yet sufficient control in the work areas of the industry, but at present the requirement of the law are beginning to realize the respective measurements and assessments to take corrective actions against the effects caused by exposure to noise. The consequences and the effects that exposure to occupational noise is labor hearing loss so a prevention and safety plan was raised against the risk factors that cause hearing loss work to give a solution to the results of the measurement and evaluation of noise done and mitigate exposure preventing the occurrence of occupational diseases by the result of Noise